Protocol: Triple Diamond method for problem solving and design thinking. Rubric validation - Juan A. Marin-Garcia; Julio J. Garcia-Sabater; Jose P. Garcia-Sabater; Julien Maheut (WPOM : Working Papers on Operations Management, 2020)
There is a set of tools that we can use to improve the results of each of the phases that continuous improvement projects must go through (8D, PDCA, DMAIC, Double diamond, etc.). These methods use divergent techniques, which help generate multiple alternatives, and convergent techniques that help analyze and filter the generated options. However, the tools used in all those frameworks are often very similar. Our goal, in this research, is to develop a comprehensive model that allows it to be used both for problem-solving and for taking advantage of opportunities. This protocol defines the main terms related to our research, makes a framework proposal, proposes a rubric that identifies observable milestones at each stage of the model and proposes the action plan to validate this rubric and the model in a given context. The action plan will be implemented in a future research.